Pains and gains of international research collaboration with academia: Perspectives from an extramural research institute - Roesel, Kristina; Grace, Delia (International Livestock Research Institute, 2018)
The International Livestock Research Institute (ILRI) is an international, independent, non-profit organization with the aim to improve food and nutritional security and to reduce poverty in developing countries through research for efficient, safe and sustainable use of livestock. Collaboration with academia has long been an integral part of ILRI’s work as it leads to shared learning, sharing of resources, synergies, complementarity and shaping of a new generation of scientists and, potentially, decision-makers.